Trends in the digitalisation of public administrations – in light of EU legislation and domestic developments - Adrián, Fábián (Central European Public Administration Review, 2023)
Purpose: Regulating the parameters of all types of identity – including its elements, authenticity and authenticator, verifiability, and the verification process – requires particular attention. The most critical element here is most likely its presence in the digital sphere. Our main goal is to examine the proposal to amend the eIDAS2 Regulation to create a frame-work for a European digital identity. Design/Methodology/Approach: The paper analyses the topic in terms of Union law and the most recent strategic document of the Hungarian governmental decisionmaker, incorporating pertinent scientific findings. The article evaluates the current situation, highlighting foreseeable and potential impacts of the new legislative developments. Findings: The paper presents both the practices established by the eIDAS Regulation as a starting point and the current status of digitalisation in Hungary (primarily in public administration). Practical Implications: Eventually, we will attempt to identify the expected opportunities and advantages, as well as risks and drawbacks, associated with the nascent trend of digitalization of public administration in the EU and Hungary.
Keywords: digitalizacija; digitalna identiteta; eIDAS 2.0; elektronsko poslovanje; e-uprava; osebni podatki; varstvo podatkov